COMMUNITY CRIMINAL RESPONSIBILITY FOR DISSEMINATION OF NEWS CONTAINING SARA THROUGH SOCIAL MEDIA: PERTANGGUNGJAWABAN PIDANA KOMUNITAS PENYEBARAN BERITA BERMUATAN SARA MELALUI MEDIA SOSIAL - Aurellya Desita Ananda Putri; Vena Safira Adelita; Maria Gabrielle Janice Angelie Siregar (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
In this millennial era, sharing and accessing information and news is very easy. This is because technology has increasingly developed among the people. People easily access information and news through social media. The government made a regulation related to the problem, namely the ITE Law. Along with the times, the provocative issue of spreading news containing SARA (Tribe, Religion, Race and Intergroup) also emerged in the use of social media because of the use of free and easy media. If the subject in question is a community as an example of a case for the spread of hate speech containing SARA Saracen. In this thesis will discuss the criminal liability of the SARA news disseminating community, using normative juridical legal research methods and accompanied by a statute approach and conceptual approach. The results of the research conducted by the author show that criminal liability in the community for distributing SARA-charged news is imposed by individuals rather than a community by adhering to the vicarious liability doctrine and that criminal sanctions are subject to article 28 paragraph (2) of the ITE Law.